2002
DOI: 10.1115/1.1460913
|View full text |Cite
|
Sign up to set email alerts
|

3-D Transonic Flow in a Compressor Cascade With Shock-Induced Corner Stall

Abstract: An experimental and numerical study of the transonic flow through a linear compressor cascade with endwalls was conducted. The cascade with a low aspect ratio of 1.34 was tested at an inlet Mach number of 1.09 and a Reynolds number of 1.9×106. Detailed flow visualizations on the surfaces and five-hole probe measurements inside the blading and in the wake region showed clearly a three-dimensional boundary layer separation on the blade surface and the sidewall, and a severe corner stall induced by a strong 3-D s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…Two possible mechanisms for how corner flows affect the centreline are proposed: Firstly, large corner flow separations may cause a large three-dimensional bifurcation of the shock wave structure that spans a significant proportion of the wind tunnel and has an effect on the amount of pressure smearing experienced by the tunnel wall boundary layers. This is in agreement with the findings of previous authors such as Weber et al (2002) and Handa, Masuda & Matsuo (2005), who observed that the 3-D (bifurcated) shock structure produced in a confined transonic SBLI increased the amount of pressure smearing near the corners. Secondly, corner flow separations may act as an effective blockage to the core flow in the tunnel and (depending on their size and relative positions) could decelerate the (supersonic) pre-shock flow and/or re-accelerate the (subsonic) post-shock flow, both of which would act to smear the adverse pressure gradient imposed by the normal shock wave.…”
Section: Review Of Factors Affecting Separation In Normal Sblissupporting
confidence: 93%
“…Two possible mechanisms for how corner flows affect the centreline are proposed: Firstly, large corner flow separations may cause a large three-dimensional bifurcation of the shock wave structure that spans a significant proportion of the wind tunnel and has an effect on the amount of pressure smearing experienced by the tunnel wall boundary layers. This is in agreement with the findings of previous authors such as Weber et al (2002) and Handa, Masuda & Matsuo (2005), who observed that the 3-D (bifurcated) shock structure produced in a confined transonic SBLI increased the amount of pressure smearing near the corners. Secondly, corner flow separations may act as an effective blockage to the core flow in the tunnel and (depending on their size and relative positions) could decelerate the (supersonic) pre-shock flow and/or re-accelerate the (subsonic) post-shock flow, both of which would act to smear the adverse pressure gradient imposed by the normal shock wave.…”
Section: Review Of Factors Affecting Separation In Normal Sblissupporting
confidence: 93%
“…12). This three-dimensional flow structure for corner separation was first derived by Schulz et al [5] and has been proved by other researchers by numerical simulations [3,7,13,26]. The appearance of the limiting streamlines for the type B flow can be seen in Fig.…”
Section: Topological Analyses Of Typical 3d Flow Structuresmentioning
confidence: 69%
“…In the experiments conducted by Schulz et al [5], they did not observe this type of flow. However, according to the numerical simulation results given by Hah and Loellbach [7] and Weber et al [26], the corner separation of flow type C may occur when the back pressure decreases below a certain value. Thus to say, the flow topology of the corner separation may appear as flow type B or C, depending on the compressor operating condition and the flow interactions inside the flow passage.…”
Section: Topological Analyses Of Typical 3d Flow Structuresmentioning
confidence: 96%
“…CFD application to a highspeed compressor cascade is more difficult because of the more severe corner separations and fully developed flow unsteadiness. Even so, studies on high-speed compressor cascades have greatly benefited from the robust RANS methods (Chen et al, 2014;Gmelin, Thiele, & Liesner, 2011;Hergt, Meyer, & Engel, 2013;Hergt, Meyer, Liesner, & Nicke, 2011;Weber, Schreiber, Fuchs, & Steinert, 2002). The turbulence models applied in the previous highspeed compressor cascade studies were carefully selected eddy viscosity models, which can easily diverge.…”
Section: Introductionmentioning
confidence: 99%